Comparative Analysis of the Diversity of SARS-CoV-2 Lines Circulating in Omsk Region in 2020–2022 - E. A. Gradoboeva; Zh. S. Tyulko; A. V. Fadeev; A. G. Yakimenko; V. V. Yakimenko (Эпидемиология и вакцинопрофилактика, 2023)
Relevance. To date, no detailed analysis of the variants of the pathogen circulating at different times on the territory of the Omsk region has been carried out.Aim. Comparative analysis of the diversity of circulating variants of SARSCoV-2 based on molecular genetic data, determine the lines and time of their appearance, compare the data obtained with data from the GISAID database.Materials and methods. Genomewide sequencing of 222 primary and 5 culture (passages on Vero E6 and SPEV cell cultures) samples of SARS-CoV-2 from the Omsk region, collected from April 2020 to February 2022, on Oxford Nanopore Technologies and Illumina platforms, was carried out. Genetic lines were determined in Pangolin. The analysis was performed in MEGA7 and BioEdit.Results. 227 genomewide SARS-CoV-2 sequences were obtained. 222 genomes have been uploaded to the GISAID database. The lines to which the samples belong were determined, phylogenetic trees were constructed for various regions of the SARS-CoV-2 genome, the levels of virus homology were assessed and mutations in the Sprotein region were analyzed.Conclusions. According to the data obtained, it is possible to roughly judge the time of the appearance of a particular variant, its consolidation and distribution in the population, and observe the rare mutations and the circulation of some rare lines. To assess the possibility of significant geographically linked changes in the SARS-CoV-2 in the Omsk region, the data obtained are insufficient. Virus variants circulating in the region are grouped into one cluster with identical variants from other regions or countries. A more pronounced intracluster differentiation of the lines can be observed when analyzing the RBD region. The situation with COVID-19 in the Omsk region generally coincides with that in the whole country and the world. However, this does not exclude the parallel occurrence of certain mutations in remote territories from each other.